Metagenomic profiling of the insect-specific virome in non-urban mosquitoes (Culicidae: Culicinae) from Colombia’s Northern inter-Andean valleys - Andrés Gómez-Palacio; Howard Junca; Rafael J. Vivero-Gomez; Juan Suaza; Claudia X. Moreno-Herrera; Gloria Cadavid-Restrepo; Dietmar H. Pieper; Sandra Uribe (PLoS ONE, 2025)
Hematophagous mosquitoes are major vectors of diverse pathogens and serve as bioindicators in tropical ecosystems, yet their virome in non-urban Neotropical regions remains poorly characterized. We analyzed the virome of 147 mosquitoes from two natural ecosystems in Colombia using a hybrid viral identification approach, combining high-confidence and less stringent methods. Most high-confidence viral contigs remained unclassified or unknown, as expected for metagenomic surveys in novel ecosystems. However, members for the Magrovirales and Ortervirales, and other six orders were detected at lower abundance. Using a complementary, less stringent approach, we identified 168 viral species from 68 genera and 22 families across four mosquito tribes (Aedini, Culicini, Orthopodomyiini, Sabethini), with dominance of Metaviridae, Retroviridae, Iridoviridae, and Poxviridae, though many sequences could not be taxonomically assigned. Insect-specific viruses predominated, while no medically relevant arboviruses were detected. Both methods consistently identified Trichoplusia ni TED virus, Cladosporium fulvum T-1 virus, Lymphocystis disease viruses, and Oryctes rhinoceros nudivirus among the most abundant and frequently detected taxa across samples. Alpha diversity indices revealed the highest virome diversity in Sabethini, followed by Orthopodmyiini, and substantially lower richness and diversity in Aedini and Culicini. These results provide a baseline for virome characterization in sylvatic mosquitoes from Colombia and highlight the need for further research on the ecological roles of the mosquito virome in pathogen transmission and microbiome evolution.